Addressing Challenges to Homeland Security Information Sharing in American Policing: Using Kotter's Leading Change Model. (October 2019) - Lambert, David E.
The sharing of homeland security information is a crucial aspect of modern policing in the United States. This article outlines some of the obstacles to information sharing at the state and local levels, including interagency and intra-agency issues that arise for police agencies. It explores the complexities of information sharing across a highly decentralized policing system. Many police departments lack a formal intelligence function that limits their ability to share information. This article offers an organizational change model using John Kotter's Leading Change principles that police agencies of any size can follow. It outlines Kotter's eight-stage process from establishing a sense of urgency through anchoring new approaches in the culture to create a framework for police departments to integrate homeland security information sharing. Its intent is to provide a framework for police agencies to incrementally implement some of the recommendations of the various strategic documents that guide information sharing.